Pengembangan Paket Modul Cetak Mata Pelajaran Pendidikan Agama Kristen SMP Negeri Tidore Kepulauan - Jhoni Lagun Siang; Nurdin Ibrahim; Rusmono - (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2017)
The purpose of this research is to produce a learning module of Christian education for students of SMP class VIII. The methodology used is research and development method. In the development using the Derek Rowntree model consisting of three stages, namely the planning stage, preparation phase of writing, and the stage of writing and editing. The product test phase begins with the validation of the material expert, and the media expert. Then after repaired the product was tested to a number of grade VIII students, ie 3 students for individual evaluation and 30 people for field evaluation. The results show the average value of material experts 3.77 which means the product is considered very good and from media experts 3.78 which means the product is considered very good. Then in the trial stage the average yield for the individual test phase 3.63 which means the product is considered very good and at this stage the field trials test 3.98 is considered very good. Based on interviews to teachers obtained very good results. The print module of Christianity education subject of SMP Negeri Kota Tidore Kepulauan is worthy to be used in the field.